Age of peak performance of elite women`s soccer players - Barreira, J. (International Journal of Sports Science, 2016)
The aim of this study was to identify age of peak performance of elite women's soccer players and to analyze the relationship between average age and national team`s performance in London 2012 Olympic Games. Data from all the 256 female soccer players registered in the tournament were collected. From each player were collected the nationality and birth day which was used to calculate athlete`s age during the championship. All data were collected at FIFA official website. Athletes showed an average age of 25,4±4,4 years. Teams that were not qualified for the quarter-finals were younger, with an average age of 22,1±3,3 years. Teams with the best classifications in the championship had the highest average ages (>26 years). These results reinforce the need to prolong women`s soccer players` career, thought a greater support for the athletes, allowing their physical, technical and tactical development throughout a long-term training program.